Immunoglobulin-mediated immune dysregulation in recurrent pregnancy loss: mechanisms, biomarkers, and therapeutic perspectives - Kamala C; Pallavi Shekar; Umme Kulsum; Ananya Hegde; Lakshitha V Jayakrishna; Deepa Bhat; Meghana Hangala Shivakumaraswamy; Akila Prashant; Praveen Kumar K S (Immunologic Research, 2026)
Recurrent pregnancy loss (RPL) is a multifactorial reproductive disease that is typified by repeated pregnancy loss with immune dysregulation emerging as a critical contributing factor. Immunoglobulins are among the immune components that are instrumental in preserving tolerance between the mother and the fetus, regulating inflammatory responses, and supporting placental development. This review provides a comprehensive overview of the role of immunoglobulins in recurrent pregnancy loss, with particular emphasis on immune dysregulation, emerging biomarkers, and therapeutic implications. The immunoglobulin profiles, such as the changes in IgG subclasses and the presence of pathogenic autoantibodies, e.g. antiphospholipid and antinuclear antibodies, are highly correlated with unfavourable pregnancy outcomes. These changes, in a mechanistic manner, lead to poor trophoblast invasion, endothelial dysfunction, thrombosis and cytokine imbalance. Emerging evidence also highlights the contribution of regulatory B cells and the antibody-mediated immune network in maintaining pregnancy homeostasis. Immunoglobulin profiling has clinical potential as a diagnostic and prognostic methodology that can be used to stratify patients and provide customised therapy. Immunomodulatory therapies, especially intravenous immunoglobulin (IVIG), are potentially effective in a limited range of patient populations, but clinical response is variable. On the whole, this review demonstrates the role of immunoglobulin-mediated mechanisms in RPL and their future potential in enhancing precision medicine approaches to better diagnosis and management.